Correlation between Organelle Genetic Variation and RNA Editing in Dinoflagellates Associated with the Coral Acropora digitifera. (27th February 2020) - Shoguchi, Eiichi; Yoshioka, Yuki; Shinzato, Chuya; Arimoto, Asuka; Bhattacharya, Debashish; Satoh, Noriyuki
Abstract: In order to develop successful strategies for coral reef preservation, it is critical that the biology of both host corals and symbiotic algae are investigated. In the Ryukyu Archipelago, which encompasses many islands spread over ∼500 km of the Pacific Ocean, four major populations of the coral Acropora digitifera have been studied using whole-genome shotgun (WGS) sequence analysis (Shinzato C, Mungpakdee S, Arakaki N, Satoh N. 2015. Genome-wide single-nucleotide polymorphism (SNP) analysis explains coral diversity and recovery in the Ryukyu Archipelago. Sci Rep. 5:18211.). In contrast, the diversity of the symbiotic dinoflagellates associated with these A. digitifera populations is unknown. It is therefore unclear if these two core components of the coral holobiont share a common evolutionary history. This issue can be addressed for the symbiotic algal populations by studying the organelle genomes of their mitochondria and plastids. Here, we analyzed WGS data from ∼150 adult A. digitifera, and by mapping reads to the available reference genome sequences, we extracted 2, 250 sequences representing 15 organelle genes of Symbiodiniaceae. Molecular phylogenetic analyses of these mitochondrial and plastid gene sets revealed that A. digitifera from the southern Yaeyama islands harbor a different Symbiodiniaceae population than the islands of Okinawa and Kerama in the north, indicating that the distribution of symbiont populations partially matches that of the four host populations. Interestingly, we found that numerous SNPs correspond to known RNA-edited sites in 14 of the Symbiodiniaceae organelle genes, with mitochondrial genes showing a stronger correspondence than plastid genes. These results suggest a possible correlation between RNA editing and SNPs in the two organelle genomes of symbiotic dinoflagellates.